Emerging role of sphingolipids and extracellular vesicles in development and therapeutics of cardiovascular diseases - Bhat, Owais Mohmad; Mir, Rakeeb Ahmad; Nehvi, Iqra Bashir; Wani, Nissar Ahmad; Dar, Abid Hamid; Zargar, M Afzal (International journal of cardiology. Heart & vasculature, 2024)
•Highlight the role of Sphingolipid pathway in CVDs and biogenesis and secretion ofsmall extracellular vesicles (sEVs)/ exosomes.•The manuscript highlights the role of exosomes as possible indicators for the onset of CVDs, linking various cellular signaling pathways that contribute to the disease progression.•Overall manuscript provides deep insights of sphingolipids and their physiological roles that may serve as appropriate platform to develop new therapeutics or adjuvant therapy for more effective treatment strategy against the CVDs. Sphingolipids are eighteen carbon alcohol lipids synthesized from non-sphingolipid precursors in the endoplasmic reticulum (ER). The sphingolipids serve as precursors for a vast range of moieties found in our cells that play a critical role in various cellular processes, including cell division, senescence, migration, differentiation, apoptosis, pyroptosis, autophagy, nutrition intake, metabolism, and protein synthesis. In CVDs, different subclasses of sphingolipids and other derived molecules such as sphingomyelin (SM), ceramides (CERs), and sphingosine-1-phosphate (S1P) are directly related to diabetic cardiomyopathy, dilated cardiomyopathy, myocarditis, ischemic heart disease (IHD), hypertension, and atherogenesis. Several genome-wide association studies showed an association between genetic variations in sphingolipid pathway genes and the risk of CVDs. The sphingolipid pathway plays an important role in the biogenesis and secretion of exosomes. Small extracellular vesicles (sEVs)/ exosomes have recently been found as possible indicators for the onset of CVDs, linking various cellular signaling pathways that contribute to the disease progression. Important features of EVs like biocompatibility, and crossing of biological barriers can improve the pharmacokinetics of drugs and will be exploited to develop next-generation drug delivery systems. In this review, we have comprehensively discussed the role of sphingolipids, and sphingolipid metabolites in the development of CVDs. In addition, concise deliberations were laid to discuss the role of sEVs/exosomes in regulating the pathophysiological processes of CVDs and the exosomes as therapeutic targets.